2006
DOI: 10.1530/rep-06-0054
|View full text |Cite
|
Sign up to set email alerts
|

Early zygotes are suitable recipients for bovine somatic nuclear transfer and result in cloned offspring

Abstract: Cloning by somatic cell nuclear transfer (SCNT) subverts sperm-mediated fertilization that normally leads to physiological activation of the oocyte. Therefore, artificial activation is required and it is presently unclear what developmental consequences this has. In this study, we aimed to improve cattle cloning efficiency by utilizing a more physiological method of activating SCNT reconstructs. We carried out in vitro fertilization (IVF) of zona-intact bovine oocytes before SCNT. We removed the zona pellucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 67 publications
(56 reference statements)
1
27
0
1
Order By: Relevance
“…In vitro production of embryos IVM oocytes were derived from Holstein-Friesian dairy cows as described (Schurmann et al 2006). IVM oocytes were fertilised at 20 to 22 h post-start of maturation as described previously (Thompson et al 2000).…”
Section: Incubation Of Sperm With Plasmid Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro production of embryos IVM oocytes were derived from Holstein-Friesian dairy cows as described (Schurmann et al 2006). IVM oocytes were fertilised at 20 to 22 h post-start of maturation as described previously (Thompson et al 2000).…”
Section: Incubation Of Sperm With Plasmid Dnamentioning
confidence: 99%
“…Then motile spermatozoa were collected after centrifugation at w1200 g for 20 min at room temperature and washed twice in TALP and then incubated with pEpi or pMax-GFP (1!10 6 spermatozoa with 1 mg plasmid in 60 ml of fertilisation medium). Fertilisation was performed in 50 ml IVF-SOF over a 24 h period as described (Schurmann et al 2006). For IVC, ten embryos were pooled in 10 ml ESOF medium and cultured for 7 days (D0: fertilisation).…”
Section: Incubation Of Sperm With Plasmid Dnamentioning
confidence: 99%
“…Recent studies, in which pronuclei were punctured before enucleation [27] or when enucleation was done before pronuclei formation [28], have proved that zygotes can also be successfully used as nuclear transfer recipients. In addition, Egli et al [7] showed that mouse zygotes temporarily arrested in mitosis could fully support somatic cell reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the ooplasm of oocytes arrested at metaphase can support efficient nuclear reprogramming of transferred nuclei. More recently, early bovine zygotes were shown to support development of transferred somatic G1 phase nuclei when the maternal telophase II chromosomes and condensed sperm DNA were removed prior to pronuclei formation (Schurmann et al, 2006). In addition, the cytoplasm of enucleated prometaphase I (pro-MI) stage oocytes was found to be capable of remodeling ES cell nuclei, resulting in pseudo-pronuclei formation (Gao et al, 2002).…”
Section: Localization Of Nuclear Reprogramming Factorsmentioning
confidence: 99%